HIV/AIDS KNOWLEDGE IMPROVES ANTIRETROVIRAL DRUG COMPLIANCE - Rifqian, Naufal; Mediana, Dian (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2024)
Antiretroviral (ARV) therapy compliance is very important for people living with HIV/AIDS (PLWHA) and their support group. Effective ARV medication was essential for HIV infected patients to improve their health, reduce progression, reduce HIV drug resistance, prolong patient life expectancy, and decrease risk of HIV/AIDS transmission to others. Many factors caused non-adherence to ARV drugs. This study aimed to determine the relationship between education, HIV/AIDS knowledge level and ARV compliance. This study was cross-sectional design using consecutive non-random sampling with total sample of 34 subjects. Data were collected using questionnaire. The number of subject conducted in Public Heatlh Center of Cibatu District, Cikarang, Indonesia from October to November 2018. Chi-Square and Fisher test was used to analysed data. Most of the respondents were males, 20-25 years old, intermediate education, HIV/AIDS knowledge level was high, and had good ARV compliance level. There was a significant relationship between education, HIV/AIDS knowledge and ARV medication compliance.